Stress, Stressors and Coping Methods Among First Year Dental Undergraduate Students: A Qualitative Study - Nagashree S Ravindranath; Manjunath P Puranik (RGUHS Journal of Dental Sciences)
Introduction The first year dental undergraduate students are in the transition phase between pre-university and university education. Dental students may experience stress during this transition.Aim To assess first year dental undergraduate studentsrsquo perspectives on stress stressors and coping.Methods Four focus group discussions were conducted during July 2022 with eight first year dental undergraduate students in each group. Participants were selected through purposive sampling from a dental college in Bengaluru India. Structured questionnaire was used to collect demographic data. A discussion guide was developed and pilot tested. Focus group discussions were carried out in a class room in the presence of a moderator recorders and participants. The discussion continued till no further themes emerged. The discussions were audio recorded transcribed verbatim and codes were developed both deductively and inductively. Coding was done and analyzed using QDA Miner Lite Software.Results Stress was perceived to be a common problem. Exams were the main source of stress followed by comparison with others and syllabus load. Concerns regarding future were felt as a strong stressor. Foremost effects of stress were reported as becoming quiet experiencing anger and hampered thinking. Music speaking with parents and friends were the coping methods considered as most effective. Participants suggested incorporation of extracurricular activities in college as a measure to reduce stress.Conclusion Stress among first year dental undergraduate students is an important issue. Suitable measures need to be taken to reduce the stress.